The activated iron system for phosphorus recovery in aqueous environments. (April 2018) - Wan, Jun; Jiang, Xiaoqing; Zhang, Tian C.; Hu, Jiong; Richter-Egger, Dana; Feng, Xiaonan; Zhou, Aijiao; Tao, Tao
Abstract: Finding a good sorbent for phosphorus (P) recovery from the aquatic environment is critical for preventing eutrophication and providing P resources. The activated iron system (mainly consisted of zero-valent iron (ZVI), Fe3 O4 and Fe 2+ ) has been reported to exhibit a favorable performance towards various contaminants in wastewater, but its effect on P recovery has not been studied systematically. In this study, we used Fe 2+ -nitrate pretreatment reaction to prepare the activated iron system and then applied it to P recovery. Results show that more than 99% P was removed from water in 60 min; co-existing anions (NO3 −, Cl − and SO4 2− ) and natural organic matter (NOM) had little effect on P removal. The P removal capacity of activated iron system is very high compared with currently reported sorbents. Externally-supplied Fe 2+ plays an important role on P removal in the system. Regeneration study shows that the activated iron system exhibited stable P recovery ability by using 0.1 M NaOH solution. Various methods were applied to characterize the ZVI and iron corrosion, and results conclude that sorption precipitation, and co-precipitation contribute to P removal. This method will be promising and have an application potential in the field for efficient and cost-effective recovery of P with cheap microscale zero valent iron. Highlights: Activated iron system was prepared using nitrate and Fe 2+ to pretreat Fe 0 . Co-existing anions and NOM had little effect on P removal. Fe 2+ plays an important role in P removal. Activated Iron system is a promising technology for P removal and recovery.